Estimasi Kedalaman Sumber Anomali Regional dan Analisis Mekanisme serta Pola Kelurusan Sesar Musi Menggunakan Metode Gaya Berat - Fatimah, Rizkahana; Yusuf, Mahmud (Jurnal Geofisika, 2025)
Musi Fault is one of the segments of the Semangko Fault (Great Sumatra Fault) that triggered the M6.0 Curup earthquake on December 15, 1979. Until now, the Musi Fault is still recorded as an active fault with a slip rate of 13.5 mm/year. The location of the Musi Fault is at 102.2º East - 102.9º East and 3.2º East - 3.9º East. This region is a part of a growing tourism industry, while there are risks due to seismic activity and seismicity in the region. Therefore, it is necessary to analyze the gravity in the Musi Fault area. This study aims to determine the estimated depth of the regional anomaly source zone based on the results of spectrum analysis. Then, derivative analysis is also carried out to identify the mechanism and location of faults so that a picture of the alignment pattern of the Musi Fault can be obtained. The method used in this research is the gravity method using data from GGMplus, Batnas, Demnas, and other supporting data used to validate the analysis results. The spectrum analysis results show that the estimation of the regional zone depth reaches 1,366.8 meters and the residual zone depth reaches 128.69 meters. The results of derivative analysis using Surfer 14 are displayed in a curve to obtain the fault location boundary which is then displayed in a map showing that the Musi Fault has a northwest - southeast alignment pattern. The fault mechanism is dominated by shear faults and there are several points that tend to be oblique. The analysis results are in accordance with previous studies, which state that the Musi Fault has a strike slip mechanism.